The Turkish Future Marker - Yavas, Feryal (Kansas Working Papers in Linguistics, 1980)
The Turkish future marker has uses which can adequately be analyzed under the modal system of the language. This lends support to the hypothesis that futurity is as much a modal notion as a temporal one.